2021
DOI: 10.21037/apm-20-2271
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of MMP-9 and sCD40L in patients with coronary slow flow

Abstract: Background: To explore the relationship between coronary slow flow (CSF) and both matrix metalloproteinase-9 (MMP-9) and soluble cluster of differentiation 40 ligand (sCD40L).Methods: Between July 2016 and September 2019, 80 patients suspected of having coronary heart disease due to chest tightness or other symptoms of chest pain and discomfort were admitted to Nanjing Jiangbei People's Hospital and, following a coronary angiography, were diagnosed as having CSF. These patients were assigned to the coronary sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Plasma soluble adhesion molecules and inflammatory markers were significantly elevated in patients with CSFP, including CRP and interleukin-6, matrix metallopro-teinase-9, soluble CD40 ligand, and CRP to albumin ratio. [18,19] However, in our study there was no significant difference in CRP between the 2 groups. This may be due to the unique characteristics of females.…”
Section: Chen Et Al • Medicine (2024) Medicinecontrasting
confidence: 69%
“…Plasma soluble adhesion molecules and inflammatory markers were significantly elevated in patients with CSFP, including CRP and interleukin-6, matrix metallopro-teinase-9, soluble CD40 ligand, and CRP to albumin ratio. [18,19] However, in our study there was no significant difference in CRP between the 2 groups. This may be due to the unique characteristics of females.…”
Section: Chen Et Al • Medicine (2024) Medicinecontrasting
confidence: 69%
“…Studies have con rmed that in ammation is a risk factor for various cardiovascular diseases [29], and in ammatory responses have also been observed in CSF [1,7]. Plasma soluble adhesion molecules and in ammatory markers were found to be signi cantly elevated in CSF patients, including C-reactive protein [30], interleukin-6 [30], platelet to lymphocyte ratio [31], neutrophil to lymphocyte ratio [32], matrix metallopro-teinase-9 and soluble CD40 ligand [33], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Tapar et al [ 29 ] found that CSF could be considered a subgroup of coronary artery diseases with increased intimal thickness in coronary arteries and extensive calcification. Some studies found that inflammatory markers, such as C-reactive protein and the neutrophil-to-lymphocyte ratio, in patients with CSF were significantly elevated compared with patients with normal coronary flow [ 30 , 31 ]. An in-depth study on the pathogenesis of CSF could provide better evidence for individualized prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%